Depiction of the Enemy in Croatia During World War I - Vukičević, Marko (Eikón / Imago, 2020)
The aim of this paper is to analyse and compare the visual representation and iconography in works depicting the enemy in Croatian visual arts during World War I. The article encompasses research on unpublished archival sources and contemporaneaous press. The works of renowned Croatian artists, who were enlisted or volunteered for frontline duty are analysed, as are the works of art presented to the Croatian general public through graphics, cartoons and caricatures in the then popular press. Comparison of war-themed images shows differences in the visualisation of the enemy. The generally accepted belief that the enemy was visually satanised and ridiculed actually only applies to caricatures and cartoons.
Keywords: World War I; Croatian Visual Artists; Stereotype; Propaganda; Political Cartoon; Caricature